EXECUTING WAR CAPTIVES BASED ON MASLAHAT: REFLECTING ON AND CONCLUDING THE CONTEMPORARY DEBATE (UUM Journal of Legal Studies, 2023)
The debate on whether war captives may be executed has been a debate among Islamic scholars since the classical era until today. Some say war captives may be executed based on maslahat, others say it is categorically impermissible. However, in recent decades, the debate on this matter has entered a new phase, with the opposing sides, i.e., permissible if maslahat is present versus the categorically impermissible, but with new arguments emerging aside from the reiteration of some classical arguments. Some of these new arguments are non-contextual, such as new conclusions derived from the known prophetic tradition (sunnah) and contextual arguments such asthe role of international law vis-a-vis Islamic law.Using the literature review as the research method this article has examined the contemporary debate and will consider both classical arguments, as well as current contextual arguments, in the light of the usu/ al-fiqh, and how international law (particularly international humanitarian law) should affect Islamic legal rulings. It is concluded that categorically prohibiting the execution of war captives is the weaker position as it relies on an incorrect interpretation of the dalil and its unrealistic application in warfare. It is also found that the position permitting captive execution if there is maslahat is, despite being often misunderstood, the stronger position, both interms of the dalil and its realistic application in warfare.